PENGARUH STRATEGI MENGAJAR GURU TERHADAP HASIL BELAJAR SISWA: KAJIAN LITERATUR - Rijkar Maulana (STKIP Subang, 2026)
Teaching strategies play an important role in determining the success of learning and student learning outcomes. A common problem in educational practice is the use of learning strategies that lack variety and are still teacher-centered, resulting in low student engagement. This study aims to examine the effect of teaching strategies on student learning outcomes based on previous research. The research method used is a descriptive qualitative approach through a literature study. Data were obtained from relevant national scientific journal articles and analyzed using content analysis techniques. The results of the study show that active, contextual learning strategies that encourage direct student involvement, such as discovery learning and problem-based learning, have been proven to increase student motivation, understanding, and learning outcomes. Conversely, passive and one-way learning strategies have less of a significant impact. Thus, the selection of appropriate teaching strategies greatly influences the improvement of learning quality and student learning outcomes.